The effect of photovoice on explicit & implicit prejudice towards persons with disability - El Zawahry, Amira (AUC Knowledge Fountain, 2018)
This study examined the effect of Photovoice on implicit and explicit prejudice towards People with Disability (PWD). Research participants (n=80) were undergraduate students at an American university in Egypt. The participants were divided into two groups; one attended an educational session on disability (n=39) while the other group attended a Photovoice exhibition (n=41). After participants attended either the educational session or the Photovoice exhibition, their level of explicit prejudice was measured using the Attitudes Toward Disabled Persons Scale (ATDP) while their level of implicit prejudice was measured using the Implicit Attitude Test (IAT). It was predicted that participants attending the Photovoice exhibition would display lower levels of both types of prejudice. However, no significant difference between the groups was found. The average scores, across the sample, showed a moderate level of both explicit and implicit prejudice towards PWD. Results were analyzed using SPSS and thematic analysis. Additionally, factors effecting research results were discussed and comparisons with similar researches were made. Finally, research limitations were highlighted and implications for future research were considered.